Complementary Feeding Practices among Mothers Having Under Two Years Children - Aryal, Yamuna; Kapali, Gayetri Darshandhari (Journal of Lumbini Engineering College, 2023)
Background:-Complementary feeding refers to the introduction of solid, semi-solid and soft food with adequate amount and frequency in addition to breast milk at six months of age of child. Timely initiation of nutritionally adequate, safe, age-appropriate complementary feeding is recommended for the better health and development of under two years children. Therefore, the main aim of the study was to find out the complementary feeding practices among mothers having under two years children. Methods:-A descriptive cross-sectional study design was used for the study. A total of 70 mothers having children of 6-24 months of age were selected from Pediatric OPD and immunization clinic, TUTH by using non-probability convenience sampling technique. Semi[1]structured interview schedule was used to identify complementary feeding practice among mothers. Data was collected from 7th to 19th August, 2022, entered in SPSS version 26 and analysis was done using descriptive and inferential statistics. Results:-The study findings revealed that the practice of exclusive breastfeeding was 78.6% and 88.6% mothers are continuing breast feeding along with complementary feeding. 55.7% of mothers timely initiated complementary feeding. Minimum Meal Frequency, Minimum Dietary Diversity and Minimum Acceptable Diet was met by 64.3%, 97.1% and 64.3% of children respectively. The status of complementary feeding practice is significantly associated with age of mother and age of child. Conclusion:-It is concluded that majority of children do not meet Minimum Dietary Diversity and Minimum Acceptable Diet. So, there is a need for interventions which encourage and aware mothers about importance of feeding adequate and minimum acceptable diet to enhance optimum growth and development of under two years children.